Involvement of the adenosine A1 receptor in the hypnotic effect of rosmarinic acid - Kim, Tae Ho; Bormate, Katrina Joy; Custodio, Raly James Perez; Cheong, Jae Hoon; Lee, Bo Kyung; Kim, Hee Jin; Jung, Yi Sook (Biomedicine and Pharmacotherapy, 2022)
Insomnia, the most common sleep disorder, is characterized by a longer sleep latency, greater sleep fragmentation, and consequent excessive daytime fatigue. Due to the various side effects of prescribed hypnotics, demand for new drugs is still high. Recent studies have suggested the adenosine receptor (AR) as a potential therapeutic target for insomnia, however, clinically useful hypnotics targeting AR are not yet available. In the present study, we evaluated the hypnotic effect of rosmarinic acid, a phenolic compound widely found in medicinal plants, through pentobarbital-induced sleep test, electroencephalography/electromyography (EEG/EMG), and immunohistochemistry in mice. The underlying mechanisms were assessed by pharmacological approach using 8-cyclopentyl-1,3-dipropylxanthine (DPCPX) and SCH5826, antagonists for A1R and A2AR, respectively. Receptor-binding assay and functional agonism were also performed. Our study provides a new evidence that rosmarinic acid has a direct binding activity (Ki = 14.21 ± 0.3 μM) and agonistic activity for A1R. We also found that rosmarinic acid significantly decreased sleep fragmentation and onset latency to NREM sleep, and these effects were abolished by DPCPX. The results from c-Fos immunostaining showed that rosmarinic acid decreased the neuronal activity in wake-promoting brain regions, such as the basal forebrain and the lateral hypothalamus, while increasing the neuronal activity in the ventrolateral preoptic nucleus, a sleep-promoting region; all these effects were significantly inhibited by DPCPX. Taken together, this study suggests that rosmarinic acid possesses novel activity as an A1R agonist and thereby exerts a hypnotic effect, and thus it may serve as a potential therapeutic agent for insomnia through targeting A1R.
Keywords: Adenosine A1 Receptor Agonists; Animals; Brain; Cinnamates; Depsides; Electroencephalography; Hypnotics and Sedatives; Male; Mice, Inbred C57BL; Mice, Inbred ICR; Neurons; Pentobarbital; Receptor, Adenosine A1; Receptor, Adenosine A2A; Sleep; 2-(Furan-2-yl)− 7-phenethyl-7 H-pyrazolo[4; 3-dipropylxanthine (PubChem CID: 1329); 3-e][1,2,4]triazolo[1; 5-c]pyrimidin-5-amine (PubChem CID: 176408); 8-cyclopentyl-1; Adenosine A1 receptor; Diazepam (PubChem CID: 3016); Insomnia; Rosmarinic acid; Rosmarinic acid (PubChem CID: 5281792); Sleep fragmentation